Arrangement of protein I in Escherichia coli outer membrane: cross-linking study. - Palva, E T (1978)
The arrangement of protein I in the outer membrane of Escherichia coli was investigated by cross-linking whole cells, isolated cell wall, protein-peptidoglycan complexes, and protein I released from peptidoglycan with NaCl. Both cleavable azide cross-linkers and imidoester reagents were used. The data presented suggest that protein I exists in the outer membrane as a trimer.